Method for preparing ammonia type ultra-pure silica sol by direct hydrolysis of nanoscale ultra-fine ultra-pure silica powder
Through the direct hydrolysis method of nano-scale ultrafine ultrapure silicon powder and using ammonia water catalysis, the problem of difficult to produce high-purity ammonia silicon sols in the existing technology is solved, and high-purity and low-cost ammonia silicon sols are prepared, which is suitable for a variety of high-purity needs.
Patent Information
- Application Number
- CN202411880353.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to produce high-purity ammonia silica sols at low cost and safely, and the existing methods have limitations in removing metal impurities, resulting in insufficient purity of the product.
The direct hydrolysis method of nano-scale ultrafine ultrapure silicon powder is used, and ammonia water is used as a catalyst to prepare high-purity ammonia silica sol by controlling the reaction conditions. There are few steps, low cost and simple operation.
The preparation of high-purity ammonia silica sol has been achieved, with metal impurities content less than 1 ppm and the purity is close to the level of preparation by method, and is suitable for chemical mechanical polishing and other fields.
Smart Images

Figure CN119591113A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano-scale silicon dioxide material synthesis, and specifically relates to a method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder. Background Art
[0002] At present, the common method for preparing ultra-high purity ammonia-type silica sol is to use hydrolyzable organosilane as the silicon source, water and alcohol as the solvent, and ammonia water as the catalyst to prepare it through hydrolysis polymerization reaction ( Method), can obtain ultra-high purity ammonia silica sol with various metal impurity content less than 1ppm; however, this method has high raw material prices, high safety risks in industrial production, and great difficulty in industrialization, so industrial production is still basically monopolized by Japan's Fuso.
[0003] In order to prepare ammoniacal silica sol using water glass or silicon powder as raw materials, generally, NaOH or KOH is used as a catalyst to prepare alkaline sodium-type or potassium-type silica sol, and then the free metal impurities in the water are removed by ion exchange, and then ammonia water is added to prepare ammonia-stabilized ammoniacal silica sol. However, the purity of the obtained product is poor and it still contains a high level of metal impurities. In addition to the various metal impurities in the raw materials that cannot be removed, the NaOH or KOH wrapped inside the nanoparticles during the growth process cannot be removed by the ion exchange method.
[0004] The ion exchange method using water glass as raw material has a high content of metal impurities in the water glass raw material. In addition to metal impurities with lower content such as Fe, Al, Ca, the content of Na ions or K ions can be as high as 5-10%. Under the current ion exchange treatment conditions, they cannot be completely removed. According to the common indicators of commercially available water glass method silica sol, Fe < 10ppm, Al < 50ppm, Ca < 5ppm are already relatively ideal effects. Na or K, which account for a high proportion of the water glass component, can also have a residual amount of tens to hundreds of ppm after treatment (calculated based on silica sol with a SiO2 content of 20-40%).
[0005] The silica sol is prepared by the hydrolysis of silicon powder. Currently, strong bases such as NaOH and KOH are mainly used as catalysts. The alkaline silica sol obtained contains a large amount of Na + , K + The alkaline silica sol is treated with ion resin to remove the Na + or K +, and then adding ammonia water can obtain ammonia-stabilized silica sol. However, because the corresponding metal ions will be wrapped inside the SiO2 nanoparticles during the particle growth process, when using cation exchange resin treatment, only the metal ions outside the particles can be removed, and the metal ions inside the particles cannot be removed. Therefore, the ammonia-type silica sol prepared by this method will also contain a considerable amount of metal ions (Na + or K + The content can still reach several hundred ppm). Some literatures also report the use of organic amines as catalysts. Although organic amines can also avoid the introduction of metal impurities, their application range in practical applications is very narrow; while ammonia-stabilized silica sol is widely used in polishing, high-end catalyst synthesis, high-temperature resistant alumina fiber synthesis and other fields. In theory, ammonia water can be directly used as a catalyst to catalyze the hydrolysis of high-purity silicon powder to prepare ultra-high purity ammonia-type silica sol products, but in fact, the current industrial silicon powder hydrolysis method for producing silica sol does not choose to use only ammonia water as a catalyst to catalyze the hydrolysis of silicon powder. This is mainly because ammonia water is too weak in alkalinity. Although it can catalyze the reaction of silicon powder, the reaction speed is very slow and the conversion rate is low. Under normal conditions, it is difficult to obtain high-purity ammonia-type silica sol products with ideal indicators through direct catalysis of ammonia water.
[0006] For example, Chinese patent document CN101585541A discloses a method for preparing electronic-grade silica sol, which uses silicon powder as raw material and is carried out in two steps: first, high-purity silica sol is prepared under catalytic conditions using silicon powder; then, the particle size is selected by a particle size selector, and impurities are removed by controlling the flow rate of the exchange liquid using an ion exchange resin, and finally, a stabilizer is added to obtain an electronic-grade silica sol with a particle size of 10-20 nm, which can be used in various technical fields of the electronics industry. Chinese patent document CN101397139A discloses a core-shell structure in which a high-purity shell is obtained by treating the surface of ordinary silica sol with high-purity siloxane, and a product with surface structure performance close to that of high-purity silica sol is obtained, but only the core of ordinary silica sol is used to reduce costs, and the shell is still made of The synthesis process, method and difficulty are There is little difference between the direct synthesis method and the method, and the overall purity of the system is not enough to meet the use of systems that require overall purity.
[0007] Therefore, it is of great significance to develop a method for preparing ultra-high purity ammonia-type silica sol with low cost and simple operation. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder. The method of the present invention can realize the direct catalysis of silicon powder hydrolysis reaction by ammonia water to prepare ultrapure ammonia-type silica sol. The key to the method of the present invention is to first prepare nano-scale ultrapure silicon powder, and by utilizing the ultra-high activity of nano-scale silicon powder materials, reduce the reaction energy barrier, so that it can produce a faster reaction speed under the condition of a small amount of ammonia water catalysis, and directly react to generate ammonia-stabilized silica sol. It has few steps, low cost, easy operation, and the purity can reach close to The degree of the method can achieve metal impurities <1ppm (depending on the different conditions of each metal impurity, ranging from several ppb to several hundred ppb).
[0009] The technical solution of the present invention is as follows:
[0010] A method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder comprises the following steps:
[0011] (1) Preparation of nano-scale ultrafine ultrapure silicon powder;
[0012] (2) adding deionized water into a reaction kettle, heating it to temperature A, adding ammonia water, and then adding nano-scale ultrafine ultrapure silicon powder slurry I to react to obtain a silica gel seed solution;
[0013] (3) Controlling the system temperature to temperature B, adding nano-scale ultrafine ultrapure silicon powder slurry II and ammonia solution to the silica gel seed solution obtained in step (2) at the same time; after the addition is completed, continuing the reaction; then raising the temperature to temperature C, performing an aging reaction, and obtaining an ammonia-type ultrapure silica sol.
[0014] Preferably, according to the present invention, the nanometer-scale ultrafine ultrapure silicon powder in step (1) is prepared from single crystal silicon with a purity of more than 99.99%; the particle size of the nanometer-scale ultrafine ultrapure silicon powder is less than 1 μm, preferably 50-500 nm; the nanometer-scale ultrafine ultrapure silicon powder is prepared according to the following method: under the protection of inert gas, a crusher made of tungsten carbide ceramic material is first used to crush the single crystal silicon block, and then an ultrafine powder multi-stage series classifier is used, and the vortex generated by the rotating turbine in the classifier is used to make the coarse particle material fall back and re-grind, and the fine powder enters the cyclone powder collector with the air flow to obtain fine powder with a particle size of less than 5 μm, and then a high-energy ball mill is used for further grinding to obtain nanometer-scale ultrafine ultrapure silicon powder with a particle size of less than 1 μm; the inert gas is argon.
[0015] Preferably, according to the present invention, the nano-scale ultrafine ultrapure silicon powder slurry I in step (2) is obtained by mixing nano-scale ultrafine ultrapure silicon powder and deionized water in a mass ratio of 1:2-20 and stirring evenly, and more preferably mixing in a mass ratio of 1:4-10.
[0016] Preferably, according to the present invention, the mass ratio of the deionized water in step (2) to the nano-scale ultrafine ultrapure silicon powder in the nano-scale ultrafine ultrapure silicon powder slurry I is 100-1000:1; and the deionized water is ultrapure water with a resistivity of 18.2 MΩ.cm.
[0017] Preferably, according to the present invention, the content of NH3 in the ammonia water in step (2) is 25-28wt%; the mass ratio of NH3 in the ammonia water to the nano-scale ultra-fine ultra-pure silicon powder in the nano-scale ultra-fine ultra-pure silicon powder slurry I is 0.005-0.05:1.
[0018] Preferably according to the present invention, the temperature A in step (2) is 50-100° C., more preferably 70-80° C.; the reaction time is 0.5-2 h, preferably 1-1.5 h.
[0019] Preferably, according to the present invention, the concentration of the nano-scale ultrafine ultrapure silicon powder slurry II in step (3) is the same as the concentration of the nano-scale ultrafine ultrapure silicon powder slurry I; the ratio of the mass of the nano-scale ultrafine ultrapure silicon powder in the nano-scale ultrafine ultrapure silicon powder slurry II to the mass of the nano-scale ultrafine ultrapure silicon powder in the nano-scale ultrafine ultrapure silicon powder slurry I is 20-30:1.
[0020] Preferably, according to the present invention, the ammonia solution in step (3) is obtained by mixing ammonia water and deionized water, the mass ratio of ammonia water to deionized water is 1:2-50, preferably 1:10-30; the content of NH3 in the ammonia water is 25-28wt%.
[0021] Preferably, according to the present invention, the mass ratio of NH3 in the ammonia solution in step (3) to the nano-scale ultrafine ultrapure silicon powder in the nano-scale ultrafine ultrapure silicon powder slurry II is 0.005-0.05:1.
[0022] Preferably, according to the present invention, in step (3), nanometer-scale ultrafine ultrapure silicon powder slurry II and ammonia solution are added simultaneously, and the addition time of nanometer-scale ultrafine ultrapure silicon powder slurry II is 5-50 hours, preferably 15-30 hours; the addition time of the ammonia solution is 10-55 hours, preferably 20-35 hours; the ammonia solution is added for 1-5 hours after the addition of nanometer-scale ultrafine ultrapure silicon powder slurry II is completed.
[0023] According to a preferred embodiment of the present invention, the temperature B in step (3) is 70-100° C., preferably 80-90° C.; after the addition is completed, the reaction time is 5-10 hours.
[0024] Preferably according to the present invention, the temperature C in step (3) is 70-100° C., preferably 90-100° C.; and the aging reaction time is 5-10 h.
[0025] Preferably, in step (3), after the aging reaction, a post-treatment step is further included, which is as follows: the obtained reaction solution is centrifuged and filtered to remove solid particulate impurities, and then concentrated to a desired concentration according to specific requirements; the further refining treatment of the silica sol after the reaction is completed is because the surface of the silicon powder will be partially oxidized when it comes into contact with air during the storage process. After the reaction is completed, the partial oxide is suspended in the silica sol in the form of larger micron-sized particles, and a small amount of solid particulate impurities need to be removed after centrifugation and filtration.
[0026] The present invention also provides an ammonia-type ultrapure silica sol prepared by the above method, wherein the particle size of the silica sol is 10-150nm, the mass percentage can be adjusted between 1-40%, the total content of metal element impurities is less than 1ppm, and the metal elements are Na, K, Fe, Al, Ca, Mg, B, Ti, Mn, Cr, Li, Ni, Cu, Zn, and Pb.
[0027] According to the present invention, the use of the above-mentioned ammonia type ultrapure silica sol in chemical mechanical polishing can meet the purity requirements of silicon wafer polishing.
[0028] According to the requirements for product concentration, it can be concentrated or diluted to the corresponding concentration.
[0029] In the present invention, in order to obtain ammonia-type ultrapure silica sol, high-purity silicon (Si≥99.99%) is selected as the raw material and ground to ultrafine particles <1μm. The purity and ultrafine particle size of silicon powder are both indispensable. Silicon with lower purity usually contains other metal or non-metal impurities (such as Fe, Al, Ca, P, B, etc.). In addition to being unable to react under alkaline conditions, such impurities themselves form complex lattice structures with silicon atoms, which may cause local non-reaction problems. Therefore, they generally cannot react completely, resulting in difficulty in subsequent impurity separation. Usually, the silicon powder available on the market is in the range of tens to hundreds of microns (for example, 325 mesh, 100 mesh, and 45 mesh correspond to 44μm, 149μm, and 350μm, respectively). The silicon powder used in the production of silica sol is also mostly in this particle size range. Within this particle size range, due to the low reaction activity of silicon powder, the reaction speed is very slow and the silicon powder conversion rate is low when only ammonia water is used for catalysis. Usually, the production of ammonia-stabilized silica sol uses strong bases such as NaOH and KOH to prepare silica sol products of other stabilizer types, and then after ion exchange to remove ionic impurities in water, ammonia water is added to prepare ammonia-type silica sol, but Na and K are difficult to completely remove and the purity is not high enough. By grinding high-purity silicon powder to the nanometer level, the activity of silicon powder can be significantly improved, so that it can react quickly under the conditions of ammonia water catalysis to generate ammonia-stabilized high-purity silica sol. Ultrafine silicon powder needs to be added in the form of slurry, because ultrafine silicon powder is light and easy to generate dust. If it is added directly to the reactor in dry powder state, on the one hand, it will be blown out of the reactor mouth or onto the reactor wall by the airflow in the reactor, and on the other hand, the silicon powder at the feed port will be wetted by water vapor and adhere to the inlet pipe, making it difficult to fall. General silicon powder does not have this problem and can be added in one time or in batches in dry powder state. In addition, ultrafine silicon powder has a very large specific surface area, so the reaction active sites are far greater than those of general silicon powder. It reacts quickly after entering the system, so it needs to be added slowly at a slower speed to better control the progress of the reaction. General silicon powder has low activity and few active sites, and requires a higher silicon powder concentration and alkali concentration in the system for effective reaction.
[0030] According to the present invention, after the reaction is completed, a high-concentration product with a pH value of 9 to 10 can be obtained by ultrafiltration concentration; or a relatively high amount of ammonia water in the reaction process can be removed from the system by reducing pressure concentration by utilizing the low boiling point of ammonia water to obtain a nearly neutral product with a pH value in the range of 7 to 8.
[0031] The method of the present invention can replace ammonia water with sodium hydroxide and potassium hydroxide to prepare sodium-type silica sol and potassium-type silica sol with very low content of other metal impurities. However, due to the ultra-high activity of silicon powder, compared with the general silicon powder process, a better catalytic effect can be obtained by using a smaller amount of alkali, and the reaction is more thorough (large-particle silicon powder has the problem of incomplete reaction).
[0032] The technical characteristics and beneficial effects of this preparation method are as follows:
[0033] 1. The present invention adopts the silicon powder method to directly prepare ultra-high purity large-particle silica sol, which simplifies the process and is easy to stably control the product quality, is easy to operate, and is economical and efficient.
[0034] 2. The method of the present invention has a high conversion rate of raw silicon powder, and the prepared large-particle silica sol has high purity. The present invention needs to limit the raw material ratio within the scope of the present invention. When the ammonia water is too low, the silicon powder cannot be fully reacted. If the silicon powder cannot be fully reacted, on the one hand, a large number of processes are required to separate the silicon powder from the silica sol, and on the other hand, it is extremely difficult to purify the unreacted silicon powder and continue to use it for subsequent reactions. If the silicon powder is not fully reacted, it will cause a large amount of raw material waste and increase production costs. The selection of the appropriate ratio of ammonia water should be combined with the requirements of the final product index on the one hand, and on the other hand, it should ensure that the silicon powder can react completely. Since the pH value of the silica sol generally used has certain requirements, if the proportion of ammonia water is too high, the pH value will be high. For ammonia-type silica sol, too much ammonia water also has an obvious irritating odor problem, and measures need to be taken to remove the ammonia water. The higher the ammonia water, the higher the cost of removal.
[0035] 3. The silica sol prepared by the present invention has controllable particle size and low particle size dispersion, and is suitable for the requirements of chemical mechanical polishing for abrasives.
[0036] 4. The silica sol prepared by the present invention has a high purity, reaching close to The metal impurity content standard of the method is far superior to the current conventional water glass method and silicon powder method products. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 TEM photo of nano-scale ultrafine ultrapure silicon powder used in the examples.
[0038] Figure 2 The EDS composition analysis results of the nano-scale ultrafine ultrapure silicon powder used in the examples are shown in FIG.
[0039] Figure 3 This is the particle size distribution curve of silicon dioxide nanoparticles in the ammonia high-purity silica sol prepared in Example 1.
[0040] Figure 4 This is a TEM photograph of silicon dioxide nanoparticles in the ammonia-type high-purity silica sol prepared in Example 1.
[0041] Figure 5 This is the EDS component analysis result of the silicon dioxide nanoparticles in the ammonia high-purity silica sol prepared in Example 1.
[0042] Figure 6 This is the particle size distribution curve of silicon dioxide nanoparticles in the ammonia high-purity silica sol prepared in Example 2.
[0043] Figure 7 This is a TEM photograph of silicon dioxide nanoparticles in the ammonia-type high-purity silica sol prepared in Example 2.
[0044] Figure 8 This is the EDS composition analysis result of the silicon dioxide nanoparticles in the ammonia high-purity silica sol prepared in Example 2.
[0045] Fig. 9 This is the particle size distribution curve of silicon dioxide nanoparticles in the sodium silica sol prepared in Comparative Example 1.
[0046] Fig.10 This is the EDS component analysis result of the silicon dioxide nanoparticles in the sodium silica sol prepared in Comparative Example 1.
[0047] Fig.11 This is the particle size distribution curve of silicon dioxide nanoparticles in the potassium-type silica sol prepared in Comparative Example 2.
[0048] Fig.12 This is the EDS component analysis result of the silicon dioxide nanoparticles in the potassium-type silica sol prepared in Comparative Example 2.
[0049] Fig.13 This is the particle size distribution curve of silicon dioxide nanoparticles in the ammonia-type high-purity silica sol prepared in Comparative Example 3.
[0050] Fig.14 This is the particle size distribution curve of silicon dioxide nanoparticles in the ammonia-type high-purity silica sol prepared in Comparative Example 4. DETAILED DESCRIPTION
[0051] The present invention will be described in detail below with reference to the embodiments, but is not limited thereto.
[0052] The nanometer-level ultrafine ultrapure silicon powder used in the embodiment is prepared according to the following method:
[0053] Under argon protection conditions, a tungsten carbide ceramic crusher is first used to crush single crystal silicon blocks with a purity of 99.99wt%. An ultrafine powder multi-stage series classifier is used, and the vortex generated by the rotating turbine in the classifier is used to make the coarse particles fall back and be re-ground. The fine powder enters the cyclone powder collector with the air flow to obtain fine powder with a particle size of less than 5μm, and then a high-energy ball mill is used for further grinding to obtain nano-level ultrafine particles with a particle size of less than 1μm.
[0054] The particle size of the obtained nano-scale ultrafine ultrapure silicon powder is less than 1 μm. The TEM photos of the particle size and morphology are shown in Figure 1 , EDS component analysis results are shown in Figure 2 ;Depend on Figure 1It can be seen that the silicon powder is ground to nanometer size, ranging from tens to hundreds of nanometers, less than 1 micron; Figure 2 It can be seen that except Si (99.20%) and O (0.80%), no other components were detected, and a small amount of O element was mainly caused by partial oxidation of silicon powder in the air.
[0055] The content of NH3 in the ammonia water used in the embodiment is 28wt%; the deionized water used in the embodiment is ultrapure water with a resistivity of 18.2MΩ.cm.
[0056] Example 1
[0057] A method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder comprises the following steps:
[0058] (1) Weigh 20 g of nano-scale ultrafine ultrapure silicon powder, place it in a slurry making kettle, add 100 g of deionized water, start high-speed stirring (1500 r / min) to fully mix the silicon powder and water to form nano-scale ultrafine ultrapure silicon powder slurry I, then appropriately reduce the speed (350 r / min) to maintain the mixing state of the slurry for standby use; add 5000 g of deionized water to a 10L reactor equipped with a reflux condenser and a thermometer probe, start the automatic temperature control program, heat to 80°C, and then add 2 g of ammonia water to the reactor; use a peristaltic pump (1#) to input the previously prepared nano-scale ultrafine ultrapure silicon powder slurry I into the reactor through the peristaltic pump tube for 5 minutes, and then react at 80°C for 1 hour to allow the silicon powder to fully react to obtain a silica gel seed liquid.
[0059] (2) Weigh 480 g of nano-scale ultrafine ultrapure silicon powder, place it in a slurry making kettle, add 2400 g of deionized water, start high-speed stirring (1500 r / min) to fully mix the silicon powder and water to form nano-scale ultrafine ultrapure silicon powder slurry II, then appropriately reduce the speed (350 r / min) to keep the slurry in a mixed state for later use.
[0060] Weigh 500 g of deionized water and put it into a 1000 mL beaker. Then add 23 g of aqueous ammonia and stir evenly to obtain an aqueous ammonia solution. Seal the mouth of the beaker with plastic wrap and let it stand for later use.
[0061] Use peristaltic pump (1#) again to input nano-scale ultrafine ultrapure silicon powder slurry II into the reactor through the peristaltic pump tube, which takes 20 hours, and use 100mL of deionized water to rinse the pulping kettle wall and then input them into the reactor together; while starting to input silicon powder slurry II, use peristaltic pump (2#) to input ammonia solution into the reactor through the peristaltic pump tube, which takes 25 hours; the process control system temperature of adding nano-scale ultrafine ultrapure silicon powder slurry II and ammonia solution is 80-85°C; after the ammonia solution is transported, continue to react at 80-85°C for 5 hours, then raise the temperature to 95°C, and keep it for aging for 10 hours. After the reaction, there is almost no silicon powder remaining. Cool down and centrifuge to obtain ammonia-type high-purity silica sol with a SiO2 concentration of 12.5wt%.
[0062] The ammonia-type high-purity silica sol SiO2 obtained in this example has an average particle size of 34.06nm and a dispersion of 0.168. The particle size distribution curve is shown in FIG. Figure 3 , TEM photos see Figure 4 , EDS component analysis see Figure 5 EDS test shows that except for Si (43.84%) and O (56.16%), no other components are detected. After ICP-MAS test analysis, the content of each element is extremely low, and the total metal impurity content is 0.782ppm, <1ppm, as shown in Table 1 below.
[0063] Table 1 Impurity content of each element in silica sol
[0064]
[0065] Example 2
[0066] A method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder comprises the following steps:
[0067] Weigh 500 g of nano-scale ultrafine ultrapure silicon powder, place it in a pulping kettle, add 2300 g of deionized water, start high-speed stirring (1500 r / min) to fully mix the silicon powder and water to form a silicon powder slurry, then reduce the speed appropriately (350 r / min) to keep the slurry in a mixed state for later use; weigh 500 g of deionized water, place it in a 1000 mL beaker, then add 25 g of ammonia water thereto, stir evenly to obtain an ammonia solution, seal the mouth of the beaker with plastic wrap, and let it stand for later use.
[0068] 4600 g of deionized water was added to a 10L reactor equipped with a reflux condenser and a thermometer probe, and 400 g of the silica sol obtained in Example 1 was added as a silica gel seed solution for secondary particle size growth. The automatic temperature control program was turned on and heated to 80°C; a peristaltic pump (1#) was used to input silicon powder slurry into the reactor through the peristaltic pump tube for 30 hours, and the pulping kettle wall was rinsed with 100 mL of deionized water and then input into the reactor together; at the same time, a peristaltic pump (2#) was started to input ammonia solution into the reactor through the peristaltic pump tube for 44 hours; the system temperature was controlled to be 80-85°C during the addition of silicon powder slurry and ammonia solution; after the ammonia solution was transported, the reaction was continued at 80-85°C for 5 hours, then the temperature was raised to 95°C, and the temperature was kept for aging for 10 hours. After the reaction, almost no silicon powder remained, the temperature was lowered, and after centrifugal filtration, an ammonia-type high-purity silica sol with a SiO2 concentration of 13.1% was obtained.
[0069] The ammonia-type high-purity silica sol SiO2 obtained in this example has an average particle size of 89.52nm and a dispersion degree of 0.094. The particle size distribution curve is shown in FIG. Figure 6 , TEM photos see Figure 7 , EDS component analysis see Figure 8 EDS test shows that except for Si (43.84%) and O (56.16%), no other components are detected. After ICP-MAS test analysis, the content of each element is extremely low, and the total metal impurity content is 0.873ppm, <1ppm, as shown in Table 2 below.
[0070] Table 2 Impurity content of each element in silica sol
[0071]
[0072] Comparative Example 1
[0073] A method for preparing sodium silicate sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder comprises the following steps:
[0074] (1) Weigh 20 g of nano-scale ultrafine ultrapure silicon powder, place it in a slurry making kettle, add 100 g of deionized water, start high-speed stirring (1500 r / min) to fully mix the silicon powder and water to form nano-scale ultrafine ultrapure silicon powder slurry I, then appropriately reduce the speed (350 r / min) to maintain the mixing state of the slurry for standby use; add 5000 g of deionized water to a 10L reactor equipped with a reflux condenser and a thermometer probe, start the automatic temperature control program, heat to 80°C, and then add 0.5 g of sodium hydroxide to the reactor; use a peristaltic pump (1#) to input the previously prepared nano-scale ultrafine ultrapure silicon powder slurry I into the reactor through the peristaltic pump tube for 5 minutes, and then react at 80°C for 1 hour to allow the silicon powder to fully react to obtain a silica gel seed liquid.
[0075] (2) Weigh 480 g of nano-scale ultrafine ultrapure silicon powder, place it in a slurry making kettle, add 2400 g of deionized water, start high-speed stirring (1500 r / min) to fully mix the silicon powder and water to form nano-scale ultrafine ultrapure silicon powder slurry II, then appropriately reduce the speed (350 r / min) to keep the slurry in a mixed state for later use.
[0076] Weigh 500 g of deionized water and put it into a 1000 mL beaker. Then add 9.5 g of sodium hydroxide and stir evenly to obtain a sodium hydroxide solution. Seal the mouth of the beaker with plastic wrap and let it stand for later use.
[0077] Use peristaltic pump (1#) again to input nano-scale ultrafine ultrapure silicon powder slurry II into the reactor through the peristaltic pump tube, and the speed takes 30 hours, and use 100mL deionized water to rinse the pulping kettle wall and then input it into the reactor together; at the same time as starting to input the silicon powder slurry, start using peristaltic pump (2#) to input sodium hydroxide solution into the reactor through the peristaltic pump tube, which takes 44 hours; the temperature of the silicon powder slurry and sodium hydroxide solution is added to the process control system at 80-85°C; after the sodium hydroxide solution is transported, continue to react at 80-85°C for 5 hours, then heat to 95°C, and age for 10 hours. After the reaction, there is almost no silicon powder remaining. Cool down and centrifuge to obtain sodium type silica sol with a SiO2 concentration of 12.5%.
[0078] The average particle size of SiO2 in the sodium silicate sol obtained in this comparative example is 78.04nm, the dispersion is 0.039, and the particle size distribution curve is shown in FIG. Fig. 9 , EDS component analysis see Fig.10 EDS detection shows that in addition to Si (43.21%) and O (56.17%), it also contains Na (0.62%). After ICP-MAS analysis, except for the high content of Na, the content of other elements is extremely low (total content <1ppm), as shown in Table 1 below.
[0079] Table 3 Impurity content of each element in silica sol
[0080]
[0081] Comparative Example 2
[0082] A method for preparing potassium-type silica sol by direct hydrolysis of high-purity silicon powder comprises the following steps:
[0083] Weigh 500 g of high-purity silicon powder (purity of 99.99 wt %, particle size of 50-150 μm) of general particle size and set aside; weigh 500 g of deionized water and put it into a 1000 mL beaker, then add 13 g of potassium hydroxide thereto, stir evenly to obtain a potassium hydroxide solution, seal the beaker with plastic wrap, and let it stand for later use.
[0084] Add 5000g of deionized water to a 10L reactor equipped with a reflux condenser and a thermometer probe, turn on the automatic temperature control program, heat to 80°C, and then add 2g of potassium hydroxide to the reactor; add 100g of dry silicon powder, and then react for 1h to allow the silicon powder to fully react to prepare a silica gel seed solution; then add 100g of dry silicon powder every 1h, for a total of 4 times; at the same time, use a peristaltic pump to input potassium hydroxide solution into the reactor at a speed of 0.5mL / min, and the time is 16.5h; the process controls the reaction temperature at 80-85°C; after the potassium hydroxide is delivered, continue to react at 80-85°C for 5h, then heat to 95°C, and age for 10h. A small amount of silicon powder has not reacted completely. Cool down and centrifuge to obtain a potassium-type silica sol with a SiO2 concentration of 18.6%. The remaining silicon powder is collected and dried with a mass of 21g, and the reaction silicon powder accounts for 95.8%.
[0085] The average particle size of SiO2 in the potassium-type silica sol obtained in this comparative example is 52.12nm, the dispersion is 0.038, and the particle size distribution curve is shown in FIG. Fig.11 , EDS component analysis see Fig.12 , EDS detection shows that in addition to Si (42.91%) and O (56.07%), it also contains K (1.02%). After using ICP-MAS test analysis, except for the high content of K and the content of Na>1ppm, the content of other elements is extremely low (total content <1ppm), mainly because potassium hydroxide usually contains a certain amount of NaOH, as shown in Table 4.
[0086] Table 4 Impurity content of each element in silica sol
[0087]
[0088] Comparative Example 3
[0089] A method for preparing ammonia-type silica sol by direct hydrolysis of high-purity silicon powder comprises the following steps:
[0090] Weigh 500 g of high-purity silicon powder (purity of 99.99 wt%, particle size of 50-150 microns) of general particle size and set aside; weigh 500 g of deionized water, put it into a 1000 mL beaker, then add 23 g of ammonia water thereto, stir evenly to obtain an ammonia solution, seal the beaker mouth with plastic wrap, and let it stand for later use.
[0091] 5000 g of deionized water was added to a 10L reactor equipped with a reflux condenser and a thermometer probe, and the automatic temperature control program was turned on and heated to 80°C. Then 2 g of ammonia water was added to the reactor; 20 g of dry silicon powder was added thereto, and the seed solution was obtained after the reaction for 1 hour. Then 30 g of dry silicon powder was added thereto every 1 hour, for a total of 16 times (since the coarse silicon powder settled very quickly in the conveying pipeline after being dispersed into a slurry, the feeding method in Example 1 could not be used, so a method of adding a small amount of dry silicon powder multiple times was adopted, and the feeding time was close to that in Example 1. The corresponding nano-scale ultrafine powder was also not suitable for the dry powder feeding method. On the one hand, the ultrafine powder was easily blown to the upper reactor wall and the chimney pipe by the airflow in the reactor. On the other hand, due to the high reaction activity of the ultrafine powder, adding a large amount in a short period of time would cause drastic fluctuations in the reaction rate. The coarse powder activity The overall reaction rate fluctuation caused by adding a certain amount at one time is relatively small, and adding a small amount multiple times can ensure a relatively stable reaction rate); at the same time, a peristaltic pump is used to input ammonia solution into the reactor, which takes 25 hours; the temperature of the process control system for adding silicon powder and ammonia solution is 80-85°C; after the ammonia solution is delivered, the reaction is continued at 80-85°C for 5 hours, and then the temperature is raised to 95°C, and the temperature is kept for aging for 10 hours. A large amount of silicon powder has not reacted completely, and the temperature is lowered to obtain an ammonia-type silica sol with a SiO2 concentration of 1.35%, an average particle size of 192.6nm, a dispersion of 0.458, and multiple distribution peaks. The particle size is very uneven and irregular. The remaining silicon powder is collected and dried, and the mass is 465g, and the reaction silicon powder accounts for 7%. The silicon powder reacts very slowly, the unreacted proportion is high, and the product particle size is unstable, which is not suitable for the preparation and production of silica sol. See the particle size distribution curve Fig.13 .
[0092] Comparative Example 4
[0093] A method for preparing ammonia-type silica sol by direct hydrolysis of high-purity silicon powder is as described in Comparative Example 3, except that the particle size of the high-purity silicon powder is 5 to 50 microns.
[0094] The results show that a large amount of silicon powder has not reacted completely. After cooling, an ammonia-type silica sol with a SiO2 concentration of 4.76% was obtained, with an average particle size of 66.71nm, a dispersion of 0.213, multiple distribution peaks, and uneven particle size. The remaining silicon powder was collected and dried with a mass of 384g, and the reaction silicon powder accounted for 25.2%. The silicon powder had a slow reaction speed, a high proportion of unreacted products, and an unstable product particle size, which was not suitable for the preparation and production of silica sol. See the particle size distribution curve for details. Fig.14 .
Claims
1. A method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder, comprising the following steps: (1) Preparation of nano-scale ultrafine ultrapure silicon powder; (2) adding deionized water into a reaction kettle, heating it to temperature A, adding ammonia water, and then adding nano-scale ultrafine ultrapure silicon powder slurry I to react to obtain a silica gel seed solution; (3) Controlling the system temperature to temperature B, adding nano-scale ultrafine ultrapure silicon powder slurry II and ammonia solution to the silica gel seed solution obtained in step (2) at the same time; after the addition is completed, continuing the reaction; then raising the temperature to temperature C, performing an aging reaction, and obtaining an ammonia-type ultrapure silica sol.
2. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: The nano-scale ultrafine ultrapure silicon powder in step (1) is prepared from single crystal silicon with a purity of more than 99.99%; the particle size of the nano-scale ultrafine ultrapure silicon powder is less than 1 μm, preferably 50-500 nm; the nano-scale ultrafine ultrapure silicon powder is prepared according to the following method: under the protection of inert gas, a crusher made of tungsten carbide ceramic material is first used to crush the single crystal silicon block, and then an ultrafine powder multi-stage series classifier is used to use the vortex generated by the rotating turbine in the classifier to make the coarse particles fall back and re-grind, and the fine powder enters the cyclone powder collector with the air flow to obtain fine powder with a particle size of less than 5 μm, and then a high-energy ball mill is used for further grinding to obtain nano-scale ultrafine ultrapure silicon powder with a particle size of less than 1 μm; the inert gas is argon.
3. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: The nano-scale ultrafine ultrapure silicon powder slurry I in step (2) is obtained by mixing nano-scale ultrafine ultrapure silicon powder and deionized water in a mass ratio of 1:2-20 and stirring evenly, and more preferably mixing in a mass ratio of 1:4-10.
4. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: The mass ratio of the deionized water to the nano-scale ultra-fine ultra-pure silicon powder in the nano-scale ultra-fine ultra-pure silicon powder slurry I in step (2) is 100-1000:1; the deionized water is ultra-pure water with a resistivity of 18.2 MΩ.cm; The content of NH3 in the ammonia water is 25-28wt%; the mass ratio of NH3 in the ammonia water to the nano-scale ultra-fine ultra-pure silicon powder in the nano-scale ultra-fine ultra-pure silicon powder slurry I is 0.005-0.05:
1.
5. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: The temperature A in step (2) is 50-100°C, more preferably 70-80°C; the reaction time is 0.5-2h, preferably 1-1.5h.
6. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: The concentration of the nano-scale ultrafine ultrapure silicon powder slurry II in step (3) is the same as that of the nano-scale ultrafine ultrapure silicon powder slurry I; the ratio of the mass of the nano-scale ultrafine ultrapure silicon powder in the nano-scale ultrafine ultrapure silicon powder slurry II to the mass of the nano-scale ultrafine ultrapure silicon powder in the nano-scale ultrafine ultrapure silicon powder slurry I is 20-30:
1.
7. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: The ammonia solution in step (3) is obtained by mixing ammonia water and deionized water, wherein the mass ratio of ammonia water to deionized water is 1:2-50, preferably 1:10-30; the content of NH3 in the ammonia water is 25-28wt%; The mass ratio of NH3 in the ammonia solution to the nano-scale ultra-fine ultra-pure silicon powder in the nano-scale ultra-fine ultra-pure silicon powder slurry II is 0.005-0.05:
1.
8. The method for preparing ammonia-type ultrapure silica sol by direct hydrolysis of nano-scale ultrafine ultrapure silicon powder according to claim 1, characterized in that: In step (3), the nano-scale ultrafine ultrapure silicon powder slurry II and the ammonia solution are added simultaneously, the addition time of the nano-scale ultrafine ultrapure silicon powder slurry II is 5-50 hours, preferably 15-30 hours; the addition time of the ammonia solution is 10-55 hours, preferably 20-35 hours; the ammonia solution is added for 1-5 hours after the addition of the nano-scale ultrafine ultrapure silicon powder slurry II is completed; In step (3), the temperature B is 70-100°C, preferably 80-90°C; after the addition is completed, the reaction time is 5-10h; the temperature C is 70-100°C, preferably 90-100°C; the aging reaction time is 5-10h.
9. An ammonia-type ultrapure silica sol, characterized in that: The silica sol is prepared by the method of claim 1, wherein the particle size of the silica sol is 10-150 nm, the mass percentage can be adjusted between 1-40%, the total content of metal element impurities is less than 1 ppm, and the metal elements are Na, K, Fe, Al, Ca, Mg, B, Ti, Mn, Cr, Li, Ni, Cu, Zn, and Pb.
10. Use of the ammonia type ultrapure silica sol according to claim 9 in chemical mechanical polishing.
Citation Information
Patent Citations
High-purity silicasol and preparation method thereof
CN101397139A
Method for preparing electronic-grade silica sol
CN101585541A